Differential Trust and Hierarchical Regulation: A Study of the Effectiveness of Rumor Refutation on Government Micro-Blogs—Analysis Based on 1290 Rumor Refutation Messages. (23rd May 2022) - Li, Wanlian; Chen, Xing
Abstract : Purpose/Significance . This study aims to explore the differences in the effectiveness of rumor refutation dissemination on government micro-blogs and to identify factors that may lead to such differences, so as to provide reference for the management of emergencies and to improve the effectiveness of rumor refutation. Methodology/Procedure . Using Octopus software to collect data from thirty government micro-blogs, the number of retweets, likes, and comments were used as indicators of the effectiveness of refutation dissemination and different levels of government micro-blogs were used as moderating variables to construct a regression model of the effect of content features and text features on refutation dissemination. The regression model was constructed to test the moderating effects of micro-blog content and text features on the effectiveness of micro-blog refutation. Results/Conclusions . The empirical results show that whether a micro-blog is from the region or not and whether a micro-blog has a title or not have a significant effect on the effectiveness of micro-blog refutation dissemination. Therefore, refutation strategies such as combining layers, giving equal importance to content and form, and focusing on originality can be adopted to enhance the refutation effect of government micro-blogs.